The Effectiveness of Differentiating Mathematics Learning in Arithmetic Sequence to Support Computational Thinking Ability - Rahmadhani, Fitri; Mulyono, Budi; Hapizah, Hapizah (Journal La Edusci, 2024)
The purpose of this research work is to examine the impact of differentiation in mathematics on CT performance of high school learners. Using a pre-experimental one-shot case study design, the study enslisted 35 students from SMAN 8 Palembang teaching mathematics with the topic arithmetic sequences. Quantitative data revealed significant improvements in all CT components, with decomposition and pattern recognition emerging as strengths (mean score: 85.3, ttt-value;14.25, ppp value; 0.00001. Observations included quantitative results for student participation, valuable peer interactions, and appropriate and appropriate uses of Strategies CT, as well as qualitative results for the visual and tiered means of differentiation incorporated into the lesson. The work supports what can be done in terms of differentiation and the assurance of learning and competencies of learners in mathematics education for all. Still, the obstacles like the asynchronous development of abstraction and algorithmization make it pertinent for refining the directions of instructions. This theoretical and practical work advances two bodies of knowledge: incorporating CT within settings of differentiation learning and promoting interdisciplinary use of the concept. That is why future studies should be directed toward experimental application, the relation of such interventions to other mathematical concepts, and their long term outcomes.